Towards a new impact geochronometer: Deformation microstructures and U-Pb systematics of shocked xenotime - Joseph, Cilva; Fougerouse, Denis; Cavosie, Aaron; Olierook, Hugo; Reddy, Steven; Tacchetto, Tom; Quintero, R.R.; Kennedy, Allen; Saxey, David; Rickard, William (2024)
Shock-deformation microstructures in xenotime have been proposed to record diagnostic evidence for meteorite impacts. Evaluating the potential for impact-induced U-Pb age resetting of the various microstructures that form in shocked xenotime remains largely unexplored. In this study, we investigate the U-Pb systematics of shocked xenotime from three impact structures, including Vredefort (South Africa), Santa Fe (New Mexico, USA), and Araguainha (Brazil). Xenotime at these sites is found in shocked granite, impact melt rock, and as detrital grains, and preserves a range of impact-induced microstructures, including planar fractures, planar deformation bands, deformation twins, and polycrystalline neoblastic grains. Microstructures in xenotime were characterised by electron backscatter diffraction (EBSD) and then targeted for U-Pb geochronology. Secondary ion mass spectrometry (SIMS) and correlated atom probe tomography (APT) were used to determine age and element mobility mechanisms at micrometer- to nanometer-scale. At the precision of SIMS spots, grain areas characterised by lattice deformation microstructures do not show evidence of U-Pb system resetting. In contrast, some grains with neoblastic textures were found to yield impact ages, with U-Pb disturbance correlating to the extent of grain recrystallisation. The APT data showed nanoscale compositional heterogeneities in the form of Pb*-Ca enriched clusters, dislocations arrays, and grain boundaries, the latter with higher concentration of trace elements such as Si, Mg, Ca, Na, Cl, and Al. Combining microstructural, geochronological and nanoscale characterisation, this study demonstrates that neoblastic microstructures can yield accurate impact ages. Shocked xenotime with neoblastic texture is the most reliable geochronometer for dating impact events.